Association between Socio-Emotional Competence and Self-Efficacy of Nurse-Educators in Peshawar - Hina Munir, Shagufta Naz, Jamal Ud Din Khan, Tehmina Taj, Muhammad Kashif, Dildar Muhammad, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the association between socio-emotional competence and self-efficacy of nurse educators in Peshawar. Method: An analytical cross-sectional study was conducted from November 2022 to February 2023 at the Nursing Colleges of Peshawar. All nurse educators with a minimum of six months of teaching experience were included as study participants. A self-administered questionnaire was used for data collection. This questionnaire consisted of 42 items, 7 for demographic, 25 for the Socio-Emotional Competence Scale having a Cronbach alpha of 0.95, and 10 for the Teachers’ Self-Efficacy Scale with a 0.88 Cronbach alpha. Scores below the median were considered low and above the median were taken as high. SPSS version 22 was used for data analysis. Results: A total of 140 Nurse Educators participated in this study; 68(48.6%) males, and 72(51.4%) females. The majority 137(98%) of them were degree holders, while only 3(2%) were diploma holders. The results showed an X2 value of 40.3 and a p-value of 0.0001, determining a significant association between both variables. The correlation was measured through the Karl Pearson Correlation Test, resulting in 0.789, which indicates a strong positive correlation between the socio-emotional competence and self-efficacy of nurse educators. Practical Implication: Training programs for improving nurse educators’ socio-emotional competency levels are necessary to enhance their self-efficacy and create a better learning environment for future nursing generations. Developing socio-emotional competence and self-efficacy will result in suitable teaching and learning practices, which in turn will improve students’ academic performance. Conclusion: This study proved a strong association between socio-emotional competence and self-efficacy of nurse educators. Developing socio-emotional competence and self-efficacy will result in suitable teaching-learning practices, improving students’ academic performance. Keywords: Socio-emotional competence, Self-Efficacy, Educators, Nurse Educator, Nursing Faculty, Professional Development